2011
DOI: 10.1080/17461391.2011.635701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term lifestyle activity modification on adiponectin mRNA expression and plasma concentrations

Abstract: Adiponectin mRNA and plasma concentrations were reduced in obesity. Exercise training may reduce the adipose tissue (AT), although it is not well known, whether exercise - induced change in AT, increases adiponectin mRNA expression and plasma concentrations or not. Therefore, the purpose of this study was to examine the effects of short-term lifestyle activity modification (LAM) on adiponectin mRNA and plasma concentrations. Sixteen obese and overweight middle-aged men (age, 35-50 years) with type 2 diabetes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Eight studies presented their data as mean values ± standard deviations [2227, 29, 30], one as mean ± standard error of the mean [21], another as median ± standard deviation [20], and one as mean and confidence interval [28]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight studies presented their data as mean values ± standard deviations [2227, 29, 30], one as mean ± standard error of the mean [21], another as median ± standard deviation [20], and one as mean and confidence interval [28]. …”
Section: Resultsmentioning
confidence: 99%
“…Moghadasi et al's (2013) [30] study had a sample composed of just men. The average age of the participants showed a little variation between the RCTs, with averages ranging from 48 to 68 years of age.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[89][90][91][92] On the other hand, Saunders et al reported increased adiponectin plasma levels following an acute bout of exercise in sedentary obese men. 93 With regard to chronic exercise intervention, most studies using endurance type training with moderate intensity reported no change in plasma levels of adiponectin, 88,94-97 while mRNA expression in adipose tissue was found either increased 94,96 or unmodified. 97 In contrast, two studies that used chronic endurance exercise protocols reported increased plasma adiponectin levels in obese young women 98 and in overweight patients with impaired glucose metabolism 78 after the intervention period.…”
Section: Exercise and The Production Of Adipokines By Adipose Tissuementioning
confidence: 95%